Pt-Pd-F/AI203catalyst applied in the HDT process. - Balangero, Gerardo Simón; Falcón , Horacio; Beltramone , Andrea Raquel (Univesidsad Tecnológica Nacional., 2015)
The inhibiting effect of basic and non-basic nitrogen compounds on the hydrogenation of polyaromatic compounds and on the hydrodesulphurization (HDS) of dibenzothiophene (DBT) and 4,6-dimethyl dibenzothiophene (4,6DMDBT), has been investigated on Pt-Pd-F/Al2O3 and compared with a commercial NiMo hydrotreating catalyst. Langmuir-Hinshelwood type rate equations were used to describe the reaction kinetics accurately with physically meaningful and well identified parameter values. Model parameters were tuned by fitting experimental data obtained in a continuous flow reactor at 345°C, 1000 psi pressure and different contact times. Pt-Pd-F/Al2O3 was more active than NiMo catalyst and conversion remained constant during 24 h of TOS. The model was able to correctly interpret all the experimental data. Parameter estimation results showed that phenanthrene and naphthalene inhibited the tetralin hydrogenation rate, whereas naphthalene and tetralin had no appreciable effect on the rate of phenanthrene conversion. This inhibition could be explained by the competitive adsorption and was described in the kinetic model by adsorption terms obtained from the multicomponent experiments. The inhibiting effect of different nitrogen compounds on the polyaromatic hydrogenation was determined. The following nitrogen compounds were investigated in this study: quinoline, 1,2,3,4-tetrahydroquinoline, indole, and indoline. The degree of inhibition was expressed in terms of an apparent adsorption constant derived from the kinetics.The inhibiting effect on the HDS of DBT and 4,6 DBT followed the same trend
Keywords: Pt-Pd-F/AI203; HDT process